The effects of time of day and chronotype on cognitive and physical performance in healthy volunteers - Elise R. Facer-Childs; Sophie Boiling; George M. Balanos (SpringerOpen, 2018)
Abstract Background Whether you are a morning lark or a night owl has proven to be a key contributor in the timing of peak athletic performance. Recent evidence suggests that accounting for these differences, known as one's chronotype, results in significantly different diurnal performance profiles. However, there is limited research investigating multiple measures of performance simultaneously over the course of a socially constrained day. Objectives This study aimed to investigate the impact of chronotype on indices of cognitive and physical performance at different times of day in healthy volunteers. Methods We recruited 56 healthy individuals categorised as early (ECT, n = 25) or late (LCT, n = 31) chronotypes using the Munich ChronoType Questionnaire, circadian phase markers and objective actigraphy. Measures of cognitive and physical performance, along with self-reported daytime sleepiness, were taken at multiple times of day (14:00 h, 20:00 h and 08:00 h the following morning). Results Here, we find significantly different diurnal variation profiles between ECTs and LCTs, for daytime sleepiness, psychomotor vigilance, executive function and isometric grip strength. LCTs were significantly impaired in all measures in the morning compared to ECTs. Conclusion Our results provide evidence to support the notion that 'night owls' are compromised earlier in the day. We offer new insight into how differences in habitual sleep patterns and circadian rhythms impact cognitive and physical measures of performance. These findings may have implications for the sports world, e.g. athletes, coaches and teams, who are constantly looking for ways to minimise performance deficits and maximise performance gains.